Impacts of increasing maize stalk retention amount on soil respiration and temperature sensitivity - Yuan, Hongfang; Wang, Gang; Huang, Dongyan; Glatzel, Stephan; Zhuang, Jian; Jia, Honglei (International Journal of Agricultural and Biological Engineering, 2022)
Conservation tillage with maize stalk retention is an effective method to replenish soil nutrients. Nutrient availability plays a major role in the control of soil respiration (SR). However, it is not known how different degrees of maize stalk retention control SR and its temperature sensitivity (Q10). To investigate the effect of maize stalk retention amount on SR and Q10, four maize (Zea mays L.) stalk retention treatments, including (i) control treatment (CT) without maize stalk retention, (ii) standing maize stalk retention (SCR), (iii) partial maize stalk retention with ‘three-year cycle’ (TYR) and (iv) chopped maize stalk retention (CCR) was set up. In order to investigate the differences in soil nutrient, soil organic carbon (SOC) quality and soil microbial biomass among four treatments, soil analysis with 6 replicates was conducted. The experimental results showed that SR rates were 1.07, 0.88, 0.59 and 0.37 g/kg of dry soil, and the average Q10 was 1.535, 1.585, 1.62 and 1.725 for CT, SCR, TYR and CCR, respectively. Increasing maize stalk retention led to the reduction of soil microbial abundance and labile carbon compositions. Pearson correlation analysis showed that soil microbial abundance had a positive correlation with SR, while labile carbon fraction had a negative correlation with Q10. In short, increasing the amount of maize stalk retention decreases SR while increasing Q10 in northeast China. This research could provide a reference value for balancing carbon sequestration and carbon decomposition in farming practice.Keywords: stalk management, soil nutrient, carbon composition, microbial biomass, laboratory incubationDOI: 10.25165/j.ijabe.20221502.6411Citation: Yuan H F, Wang G, Huang D Y, Glatzel S, Zhuang J, Jia H L. Impacts of increasing maize stalk retention amount on soil respiration and temperature sensitivity. Int J Agric & Biol Eng, 2022; 15(2): 135–141.